ANALISIS PENGARUH STRUKTUR KEPEMILIKAN SAHAM DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN YANG TERDAPAT DI LQ 45 - B11110141, Lukman (Jurnal Manajemen Update, 2015)
The purpose of this study is to determine the effect of ownership structure that includes managerial ownership and institutional ownership and financial performance consisting of leverage, firm size as a control variable up on the value of the company. This study used a sample of 11 companies going public are contained in LQ 45 2010-2013. This study using purposive sampling method, using multiple regression analysis. The analysis finds that managerial ownership is not significant to the value of the company. Institutional ownership has no significant effect on the value of the company. Debt Ratio significant effect on the value of the company and the size of the company has a significant influence on the value of the company as measured by Tobin Q. Keywords: Ownership Structure, Leverage, Size, firm’s Value.